Two new species of Choerophryne (Anura, Microhylidae) from the northern versant of Papua New Guinea’s central cordillera - Iannella, Amy; Oliver, Paul; Richards, Stephen (Zootaxa, 2015)
We describe two new species of small microhylid frogs in the genus Choerophryne from the northern slopes of Papua New Guinea’s central cordillera. Choerophryne epirrhina sp. nov. can be distinguished from congeners by the combination of moderately small size (SUL 14.9–15.0 mm), distinctly elongated snout (OHG/SUL 0.09–0.10), first finger without expanded disk, and advertisement call consisting of 3–4 distinctly pulsed notes repeated in long sequences. Choerophryne grylloides sp. nov. can be distinguished from congeners by the combination of very small size (SUL 12.5 mm), moderately long snout (OHG/SUL 0.08), long legs (TL/SUL 0.42), first finger without expanded disk and advertisement call consisting of 4–5 distinctly pulsed notes, the last of which has many more pulses than preceding notes (9–10 vs. 3–4).